2007
DOI: 10.1055/s-2007-965015
|View full text |Cite
|
Sign up to set email alerts
|

Post-Appendectomy Intra-Abdominal Abscesses - Can They Successfully Be Managed with the Sole Use of Antibiotic Therapy?

Abstract: The results suggest that intravenous triple antibiotic therapy alone is an efficacious first-line treatment in children developing intra-abdominal abscesses following appendectomy. Surgical intervention is rarely necessary except in patients with an alarming patient status or with signs of septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 11 publications
1
18
0
5
Order By: Relevance
“…Several studies indicate that postappendectomy abscesses can be successfully managed with the sole use of antibiotic therapy; therefore, surgical intervention is rarely necessary [25][26][27][28]. In our study, the treatment of postoperative intraabdominal abscesses followed a more aggressive approach in most patients.…”
Section: Discussionmentioning
confidence: 72%
“…Several studies indicate that postappendectomy abscesses can be successfully managed with the sole use of antibiotic therapy; therefore, surgical intervention is rarely necessary [25][26][27][28]. In our study, the treatment of postoperative intraabdominal abscesses followed a more aggressive approach in most patients.…”
Section: Discussionmentioning
confidence: 72%
“…In a study by Okoye et al [6], 23 children investigated after appendectomy were found to have abdominal collections, 21 (91%) of whom recovered with antibiotics alone after an average of 8.3 days. Similarly, in a study by Forgues et al [8], 22 (85%) of 26 patients with postoperative fluid collections were successfully treated with antibiotics alone for an average of 8 days with resolution of symptoms. Although neither study defined what constituted a treatment failure, both concluded that most children improve without drainage.…”
Section: Discussionmentioning
confidence: 75%
“…One of the recent challenges in the management of complicated appendicitis is deciding whether percutaneously draining these fluid collections will have clinical benefit beyond treatment with antibiotics alone. There have been several recent studies suggesting that children will recover fully with only antibiotics in most cases [6][7][8][9]. The purpose of this study is to determine whether drainage of postoperative fluid collections hastens recovery in children after surgery for perforated appendicitis and whether drains should be placed routinely, in select cases or not at all.…”
mentioning
confidence: 99%
“…Three papers report about one intervention [3, 7, 14], one about two interventions [5] and two about three interventions [4, 6]. Treatment strategies of antibiotics, surgical drainage and radiological drainage were described in five, four and two studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Historically, PAA were therefore treated by drainage, either surgically (open or laparoscopic) or percutaneously under radiological guidance. It has been observed that noninvasive treatment (with antibiotics or even without antibiotics but with close clinical monitoring) is also effective in many cases [1, 46]. Choice of treatment not only depends on several factors including clinical, biochemical and radiological characteristics but also on preferences of individual surgeons.…”
Section: Introductionmentioning
confidence: 99%